2021
DOI: 10.1111/jpi.12760
|View full text |Cite
|
Sign up to set email alerts
|

A novel melatonin‐regulated lncRNA suppresses TPA‐induced oral cancer cell motility through replenishing PRUNE2 expression

Abstract: The inhibitory effect of melatonin on cancer cell dissemination is well established, yet the functional involvement of lncRNAs in melatonin signaling remains poorly understood. In this study, we identified a melatonin‐attenuated lncRNA acting as a potential melatonin‐regulated oral cancer stimulator (MROS‐1). Downregulation of MROS‐1 by melatonin suppressed TPA‐induced oral cancer migration through replenishing the protein expression of prune homolog 2 (PRUNE2), which functioned as a tumor suppressor in oral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 67 publications
0
40
0
Order By: Relevance
“…However, the association between PRUNE2 expression and its prognostic role in CRC requires further study. Increased methylation of PRUNE2 promoter is associated with nodal metastasis and inversely associated with PRUNE2 expression in head and neck cancer ( 25 ). Further studies are required to identify potential genes that regulate expression of PRUNE2 by regulating the promoter or methylation of PRUNE2 and thus influence the development of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between PRUNE2 expression and its prognostic role in CRC requires further study. Increased methylation of PRUNE2 promoter is associated with nodal metastasis and inversely associated with PRUNE2 expression in head and neck cancer ( 25 ). Further studies are required to identify potential genes that regulate expression of PRUNE2 by regulating the promoter or methylation of PRUNE2 and thus influence the development of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…For the migration assay: Treated cells in 0.5% FBS medium were loaded into the well of the chamber at the upper part and incubated at 37 °C in 5% CO2 for 24 h. For invasion: 10 μL Matrigel (BD Biosciences, MA, USA) was applied to 8 μm pore size polycarbonate membrane filters that included 10% FBS DMEM medium and then air-dried for 3~4 h in an incubator. The migrated and invaded cells were fixed by methanol for 10 min, stained with Giemsa and counted by light microscopy [20].…”
Section: Migration and Invasion Assaymentioning
confidence: 99%
“…Melatonin also downregulates melatonin-regulated oral cancer stimulator (MROS-1), suppressing oral migration, refilling the protein homolog 2 (PRUNE). Cell migration induced by MROS-1, modulating PRUNE2, is mediated by an epigenetic mechanism regulated by DNMT3A [ 88 ]. Surprisingly, a recent article reported that high doses of MT could reverse its protective function toward a pro-oncogenic effect.…”
Section: Melatonin a Pleiotropic Moleculementioning
confidence: 99%